Constitutive ERK1/2 activation contributes to production of double minute chromosomes in tumour cells. Issue 1 (6th November 2014) - Sun, Wenjing; Quan, Chao; Huang, Yun; Ji, Wei; Yu, Lisa; Li, Xinxin; Zhang, Yang; Zheng, Zhibo; Zou, Hongyan; Li, Quanxiao; Xu, Ping; Feng, Yan; et al.
Abstract Double minute chromosomes (DMs) are extrachromosomal cytogenetic structures found in tumour cells. As hallmarks of gene amplification, DMs often carry oncogenes and drug‐resistance genes and play important roles in malignant tumour progression and drug resistance. The mitogen‐activated protein kinase (MAPK) signalling pathway is frequently dysregulated in human malignant tumours, which induces genomic instability, but it remains unclear whether a close relationship exists between MAPK signalling and DMs. In the present study, we focused on three major components of MAPK signalling, ERK1/2, JNK1/2/3 and p38, to investigate the relationship between MAPK and DM production in tumour cells. We found that the constitutive phosphorylation of ERK1/2, but not JNK1/2/3 and p38, was closely associated with DMs in tumour cells. Inhibition of ERK1/2 activation in DM‐containing and ERK1/2 constitutively phosphorylated tumour cells was able to markedly decrease the number of DMs, as well as the degree of amplification and expression of DM‐carried genes. The mechanism was found to be an increasing tendency of DM DNA to break, become enveloped into micronuclei (MNs) and excluded from the tumour cells during the S/G2 phases of the cell cycle, events that accompanied the reversion of malignant behaviour. Our study reveals a linkage between ERK1/2 activation and DM stability in tumour cells. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.